Oral Management of Herpes-Associated Erythema Multiforme in A Microcytic Anaemia Patient - Ayuningtyas , Nurina Febriyanti; Sismiyanti, Rossy; YasminMahdani, Fatma; Dewi, Gremita Kusuma (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: One acute and self-limiting hypersensitivity reaction affecting the skin and/or other mucous membranes is known as Erythema Multiforme (EM). EM is considered to be associated with infections or medications. Infection with Herpes Simplex Virus types 1 and 2 (HSV-1 and HSV-2) is a well-known predisposing factor and the most prevalent cause of EM, also referred to as Herpes Associated Erythema Multiforme (HAEM). Case: A 31-year-old female patient presented to RSGM Universitas Airlangga with red-black crusts, erosion, and bleeding on her lips, as well as erosion and sloughing of the oral mucosa. She had experienced fever and chills for a week, and three days later, lesions appeared on the lips and oral mucosa. The symptoms progressively worsened despite treatment. Case Treatment: At the first visit, the patient was referred for serology tests, complete blood count, IgM and IgG Anti-HSV 1 and Anti-HSV 2, and total IgE. Positive serology for IgG Anti-HSV 1 confirmed the diagnosis, and microcytic anaemia was also detected. The patient was treated with steroid orabase and oral elixir, administered four times daily. Discussions: The first line in treatment management is using antiviral therapy. Early treatment with oral antivirals may lessen the number and duration of lesions. Topical steroids can be given in dosage form, paste in orabase, ointment or elixir according to the involvement of the lesion area. Conclusion: Management of HAEM must determine the etiology and symptoms. A prompt and correct diagnosis following by the right approach to oral management not only cure but also prevent recurrence and improve the quality of life.